“Does Supplementing Traditional teaching with Computer Assisted Learning (CAL) Module Facilitates Understanding of Human Embryology in Medical Undergraduates? A Randomized Control Trial” - Bhatnagar, Rajan Bhatnagar; Tandon, Aseem; Pokhrel, Rishi (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: In present scenario when lesser time is being devoted to basic medical sciences, and at the same time knowledge and concepts required to be mastered by medical undergraduates increasing exponentially, structured modules and software have a potential role to play. Embryology in particular can be a subject for such modules owing to its complex dynamics and even less proportion of time available to master it. This study evaluates if supplementing traditional methods with computer-aided instruction improve students' understanding of human embryology. Methods: The study was conducted during revision sessions before university examinations. Subjects of study were first year medical undergraduates (n=128), divided into two equal groups by simple randomization. Demographic data and prior academic performance of students were collected from student profile register. Revision sessions for control group were conducted using traditional methods and for test group CAL module was used. Students were evaluated by pre and post-tests consisting of 50 multiple choice answers questions each and each question fetched 0.5 marks. Independent sample t test was used for comparison of means. Opinion of students and instructors were collected using anonymous questionnaire under heads of subject-interest, appropriateness of CAL module as teaching materials, overall satisfaction and its possible effectiveness as self-learning module. Results: Two groups showed no statistical difference in terms of sex ratio, age and prior academic performance. Pre-test showed no significant difference in mean scores of two groups, mean post-test scores on the other hand were significantly greater in test group as compared to the control group. Most of the students and instructors involved in the study graded the CAL-module as ‘excellent’. Conclusions: The study shows that traditional teaching methods supplemented with CAL module improves the understanding of developmental anatomy in medical undergraduates. Use of this module as a self-study material requires further evaluations. doi: http://dx.doi.org/10.3126/mjsbh.v13i1.12997